2012
DOI: 10.1063/1.3673802
|View full text |Cite
|
Sign up to set email alerts
|

A tapered channel microfluidic device for comprehensive cell adhesion analysis, using measurements of detachment kinetics and shear stress-dependent motion

Abstract: We have developed a method for studying cellular adhesion by using a custom-designed microfluidic device with parallel non-connected tapered channels. The design enables investigation of cellular responses to a large range of shear stress (ratio of 25) with a single input flow-rate. For each shear stress, a large number of cells are analyzed (500-1500 cells), providing statistically relevant data within a single experiment. Besides adhesion strength measurements, the microsystem presented in this paper enables… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 39 publications
0
34
0
Order By: Relevance
“…Many devices used in the study of cell-vessel wall interactions employ a parallel-plate fl ow chamber, with recent microfabrication advancements allowing for minimization of material consumption in such devices. For example, a device developed by Rupprecht et al used variable cross-sectional area along the length of a channel to study a range of shear stresses (1-50 dyn/cm 2 ) in a single device at a single fl ow rate [ 108 ]. In order to visualize cell adhesion at a range of shear stresses within one fi eld of view, Gutierrez et al designed a microfl uidic platform that features eight parallel channels [ 109 ].…”
Section: Wall Shear Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Many devices used in the study of cell-vessel wall interactions employ a parallel-plate fl ow chamber, with recent microfabrication advancements allowing for minimization of material consumption in such devices. For example, a device developed by Rupprecht et al used variable cross-sectional area along the length of a channel to study a range of shear stresses (1-50 dyn/cm 2 ) in a single device at a single fl ow rate [ 108 ]. In order to visualize cell adhesion at a range of shear stresses within one fi eld of view, Gutierrez et al designed a microfl uidic platform that features eight parallel channels [ 109 ].…”
Section: Wall Shear Stressmentioning
confidence: 99%
“…An approximation of wall shear stress can be determined via Poiseuille's law and can be controlled by altering fl uid viscosity, fl uid fl ow rate, or channel dimensions [ 108 ]. For the study of shear stress regulated cell adhesion, microfl uidic channel design enables the manipulation of shear stress based on these three parameters.…”
Section: Wall Shear Stressmentioning
confidence: 99%
“…We used a critical adhesion strength to quantify the cell adhesion strength, a WSS level where 50% of the cells were detached after exposure to the flow as an adhesion indicator, which was generally suggested in previous studies. 11,13,17 Fig. 4(b) shows that the critical adhesion strength of the NIH-3T3 cells on the glass substrate is approximately 104.41 6 12.10 and 125.01 6 23.00 dyn/cm 2 (standard error was calculated from the linear fitting) after 2 h and 6 h of adhesion, respectively.…”
Section: B Measuring Cell Adhesion Strengthmentioning
confidence: 99%
“…21 Although there remains whether the normal adhesion force or shear adhesion strength is a suitable parameter for quantification of the cell adhesion, the cell adhesion strength with the shear stress term has been widely reported with the various cell types on the different substrates. [6][7][8][9][10][11][12][13][14]22,23 Besides, there have been attempts to demonstrate the mechanical model to estimate the magnitude of the normal force when the WSS is applied to the adhered cells to evaluate the binding force of the integrin receptors to extracellular ligands. 12,[24][25][26] Hammer et al suggested a simple mechanical model to estimate the normal adhesion force from the cell adhesion strength measured by the shear stress term.…”
Section: B Measuring Cell Adhesion Strengthmentioning
confidence: 99%
See 1 more Smart Citation